Differential Equations Solutions 39

Differential Equations Solutions 39 - 49 To verify the...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 49 To verify the secant condition, compute B(k+1) s(k) = B(k) s(k) − (B(k) s(k) − y(k) ) s(k) T s(k) s(k) T s(k) = B(k) s(k) − (B(k) s(k) − y(k) ) = y(k) , as desired. If vT s(k) = 0, then B(k+1) v = B(k) v − (B(k) s(k) − y(k) ) s(k) T v s(k) T s(k) = B(k) v, as desired. CHALLENGE 9.7. B(k+1) s(k) = B(k) s(k) − = B(k) s(k) − B(k) s(k) s(k) T B(k) s(k) + y(k) y(k) T (k) s y(k) T s(k) + y(k) y(k) T s(k) y(k) T s(k) s(k) T B(k) s(k) B(k) s(k) Bss (k ) (k ) (k ) T s(k) T B(k) s(k) s(k) T B(k) s(k) y(k) T s(k) = B(k) s(k) − B(k) s(k) + y(k) (k) T (k) (k ) (k ) y s s(k) T B s (k ) (k ) (k ) (k ) (k ) =B s −B s +y = y(k) . CHALLENGE 9.8. Dropping superscripts for brevity, and taking advantage of symmetry of H, we obtain 1 (x + αp)T H(x + αp) − (x + αp)T b 2 1 1 = xT Hx − xT b + αpT Hx + α2 pT Hp − αpT b. 2 2 Differentiating with respect to α we obtain f (x(0) + αp(0) ) = pT Hx + αpT Hp − pT b = 0, so α= pT b − pT Hx pT r =T , T Hp p p Hp where r = b − Hx. If we differentiate a second time, we find that the second derivative of f with respect to α is pT Hp > 0 (when p = 0), so we have found a minimizer. ...
View Full Document

This note was uploaded on 01/21/2012 for the course MAP 3302 taught by Professor Dr.robin during the Fall '11 term at University of Florida.

Ask a homework question - tutors are online